The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/8874747
|View full text |Cite|
|
Sign up to set email alerts
|

Isolation and Molecular Identification and Antimicrobial Susceptibility of Providencia spp. from Raw Cow’s Milk in Baghdad, Iraq

Abstract: A total of sixty raw milk samples were collected from (street vendors and shops) from Baghdad city, Iraq. The samples were inoculated into peptone water and, then, subcultured onto McConkey agar and Blood agar. Identification of isolates was confirmed by microscopic examination, cultural characteristic, biochemical tests, Vitek (VITEK®2 system), and Biolog GN substrate reactions followed by 16S rRNA and specific genes sequencing. Of 60 raw cow’s milk samples, Providencia spp. were identified only in 4 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…The isolates showed MDR to antimicrobial agents and the MAR index was more than 0.2 indicates that isolates are at risk, according to (Krumperman,1983;Magiorakos et al, 2012). The results were following other studies, which showed Providencia spp were MDR (Cao et al, 2017;Al-Gburi 2020). P. rettgeri are reported resistant to many antimicrobials such as polymyxins, first-generation cephalosporins, ampicillin, and tigecycline (Magiorakos et al, 2012).…”
Section: Biochemical Testssupporting
confidence: 83%
“…The isolates showed MDR to antimicrobial agents and the MAR index was more than 0.2 indicates that isolates are at risk, according to (Krumperman,1983;Magiorakos et al, 2012). The results were following other studies, which showed Providencia spp were MDR (Cao et al, 2017;Al-Gburi 2020). P. rettgeri are reported resistant to many antimicrobials such as polymyxins, first-generation cephalosporins, ampicillin, and tigecycline (Magiorakos et al, 2012).…”
Section: Biochemical Testssupporting
confidence: 83%
“…Verification of whether diseases caused by this bacterium can be spread through polluted water, medical wastes, feces, and contaminated food requires much work. Furthermore, we should also note that infected fish showed no symptoms on the body surface in our research, which is unexpected, and once these fish act as carriers of this bacteria, it will put humans or other animals that feed on this kind of fish in danger ( Ayyal Al-Gburi, 2020 ). We need to conduct a massive amount of future research to determine, for instance, whether new pathogens have the potential to cause transboundary transmission between different hosts.…”
Section: Discussionmentioning
confidence: 70%
“…From the comparative genome analysis, it was confirmed that this strain also shared many genes with other strains in the genome that were isolated from the environment or medical materials; it was even isolated from woodpeckers. Thus, it was suspected that a coinfection or transboundary transmission might occur from land animals or birds carrying pathogenic microorganisms to the aquatic animals ( Ayyal Al-Gburi, 2020 ). Pangenome analysis results also revealed 104 genes whose functions are associated with adaptation to living conditions with higher salinity, complex marine biomes, or lower temperature, thus improving bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, the largest number of strains were from Providencia spp. ; 1213 isolates were reported from only two studies [ 49 , 261 ]. Several varieties of bacterial strains were reported from Iraq; these included 1063 S. aureus isolated from humans [ 15 ], 142 E. coli isolated from chickens [ 37 ], and 1209 Providencia spp.…”
Section: Logical Relation Between Sets Of Multidrug-resistant (Mdr) Microbesmentioning
confidence: 99%